Myocardial protection during elective coronary artery bypasses grafting by pretreatment with omega-3 polyunsaturated fatty acids - Veljović Milić; Popadić Ana; Vukić Zoran; Ilić Radoje; Trifunović Zoran; Antunović Mirjana; Mandarić Vladimir; Tišma Svetislav; Marković Zoran (Vojnosanitetski Pregled)
Background/Aim. Despite recent advances in coronary artery bypass grafting (CABG), cardioplegic cardiac arrest and cardiopulmonary bypass (CPB) are still associated with myocardial injury. Accordingly, the efforts have been made lately to improve the outcome of CPB by glucose-insulinpotassium, adenosine, Ca2+-channel antagonists, L-arginine, N-acetylcysteine, coenzyme Q10, diazoxide, Na+/H+ exchange inhibitors, but with an unequal results. Since omega-3 polyunsatutated fatty acids (PUFAs) have shown remarkable cardioprotection in preclinical researches, the aim of our study was to check their effects in prevention of ischemia reperfusion injury in patients with CPB. Methods. This prospective, randomized, placebo-controlled study was performed with parallel groups. The patients undergoing elective CABG were randomized to receive preoperative intravenous omega-3 PUFAs infusion (n = 20) or the same volume of 0.9% saline solution infusion (n = 20). Blood samples were collected simultaneously from the radial artery and the coronary sinus before starting CPB and at 10, 20 and 30 min after the release of the aortic cross clamp. Lactate extraction/excretion and myocardial oxygen extraction were calculated and compared between the two groups. The levels of troponin I (TnT) and creatine kinase-myocardial band (CK-MB) were determined before starting CPB and 4 and 24 h postoperatively. Results. Demographic and operative characteristics, including CPB and aortic cross-clamp time, were similar between the two groups of patients. The level of lactate extraction 10 and 20 min after aortic cross-clamp time has shown negative values in the control group, but positive values in the PUFAs group with statistically significant differences (-19.6% vs 7.9%; p < 0.0001 and -19.9% vs 8.2%; p < 0.0008, respectively). The level of lactate extraction 30 minutes after reperfusion was not statistically different between the two groups (6.9% vs 4.2%; p < 0.54). Oxygen extraction in the PUFAs group was statistically significantly higher compared to the control group after 10, 20 and 30 min of reperfusion (35.5% vs 50.4%, p < 0.0004; 25.8 % vs 48.7%, p < 0.0001 and 25.8% vs 45.6%, p < 0.0002, respectively). The level of TnT, 4 and 24 h after CPB, was significantly higher in the control group compared to PUFAs group, with statistically significant differences (11.4 vs 6.6, p < 0.009 and 12.7 vs 5.9, p < 0.008, respectively). The level of CK-MB, 4 h after CPB, was significantly higher in the control group compared to PUFAs group (61.9 vs 37.7, p < 0.008), but its level, 24 h after CPB, was not statistically different between the two groups (58.9 vs 40.6, p < 0.051). Conclusion. Treatment with omega-3 PUFAs administered preoperatively promoted early metabolic recovery of the heart after elective CABG and improved myocardial protection. This study showed that omega-3 emulsion should not be considered only as a nutritional supplement but also as a clinically safe and potent cardioprotective adjunct during CPB.